Respuesta :

Answer:

see explanation

Step-by-step explanation:

(a)

9n = [tex]\frac{15}{7}[/tex] - 2 ( multiply through by 7 to clear the fraction )

63n = 15 - 14 = 1 ( divide both sides by 63 )

n = [tex]\frac{1}{63}[/tex]

(b)

[tex]\frac{1}{3}[/tex] = k - 4 ( multiply through by 3 to clear the fraction )

1 = 3k - 12 ( add 12 to both sides )

13 = 3k ( divide both sides by 3 )

[tex]\frac{13}{3}[/tex] = k

(c)

g - [tex]\frac{2}{5}[/tex] g = 3 ( multiply through by 5 to clear the fraction )

5g - 2g = 15

3g = 15 ( divide both sides by 3 )

g = 5

(d)

[tex]\frac{3}{7}[/tex] w + 2w = 3 ( multiply through by 7 to clear the fraction )

3w + 14w = 21

17w = 21 ( divide both sides by 17 )

w = [tex]\frac{21}{17}[/tex]

ACCESS MORE